Blood Progestrone Level of Intensively Managed Savanna Brown Does Fed Maize Bran and Protein Concentrate Diet - Alemede, I.C. (Pakistan Journal of Nutrition, 2009)
The effect of feeding Maize Bran and 10% crude protein concentrate diet on the blood progesterone level of intensively managed savanna brown doe was investigated. Twelve nulliparous savanna brown does with mean body weigh of 8.70±1.12 kg were used for the experiment which lasted for a period of eight weeks. The animals were randomly assigned into two groups (A and B) with a replicate each. Does in treatment A were fed diets containing 10% CP while those in treatment B had Maize Bran. Blood progesterone level were monitored 18 days prior to and 30 days following oestrus. It was observed that levels of progesterone in both groups were low prior to oestrus and mating but increased following oestrus and mating. The rate of increase was slightly higher in the group that had 10% CP diet particularly between day 21 and 27 post oestrus. Even though level of hormone in the serum of does in both groups did not differ significantly (p>0.05). It was concluded that protein have an effect on the level of circulating progesterone in the blood of Savanna Brown does. Therefore incorporation of protein into the ration of Savanna Brown does is highly recommended.